1999
DOI: 10.1038/19024
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of dynamin's GAP domain stimulates receptor-mediated endocytosis

Abstract: Dynamin is a GTP-hydrolysing protein that is an essential participant in clathrin-mediated endocytosis by cells. It self-assembles into 'collars' in vitro which also formin vivo at the necks of invaginated coated pits. This self-assembly stimulates dynamin's GTPase activity and it has been proposed that dynamin hydrolyses GTP in order to generate the force needed to sever vesicles from the plasma membrane. A mechanism is now described in which self-assembly of dynamin is coordinated by a domain of dynamin with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
365
2
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(392 citation statements)
references
References 40 publications
23
365
2
2
Order By: Relevance
“…Based on these findings, dynamin's AH domain was renamed the GED [36]. Overproduction of a dynamin GED mutation predicted to prolong the GTP-bound state was shown to enhance the rate of endocytosis in vivo, consistent with the idea that dynamin-GTP regulates a rate-limiting step in endocytosis [36]. A later study established that this rate-limiting step was the formation of constricted coated pits [35].…”
Section: Regulation By Dnm1p Occurs Via a Multistep Pathwaymentioning
confidence: 88%
See 2 more Smart Citations
“…Based on these findings, dynamin's AH domain was renamed the GED [36]. Overproduction of a dynamin GED mutation predicted to prolong the GTP-bound state was shown to enhance the rate of endocytosis in vivo, consistent with the idea that dynamin-GTP regulates a rate-limiting step in endocytosis [36]. A later study established that this rate-limiting step was the formation of constricted coated pits [35].…”
Section: Regulation By Dnm1p Occurs Via a Multistep Pathwaymentioning
confidence: 88%
“…Evidence that the GTPase cycle of Dnm1p might regulate this rate-limiting step in mitochondrial fission comes from mutational studies of the Dnm1p AH domain [28]. In previous in vitro studies of mammalian dynamin, the AH domain was shown to stimulate GTP hydrolysis by dynamin after the protein assembled to form higher-order structures [35,36]. Based on these findings, dynamin's AH domain was renamed the GED [36].…”
Section: Regulation By Dnm1p Occurs Via a Multistep Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamin, a large GTPase, forms a collar around membrane invaginations to cause scission of budding vesicles that are targetted to the endocytic membrane system. Dynamin self assembly and GTPase activity are significantly enhanced by microtubules [142][143][144]. Further dynamin has been identified in complex with actin regulators, including profilin and ROCK [145].…”
Section: Microtubule and Endocytic Regulation Of Focal Adhesionsmentioning
confidence: 99%
“…It is believed to have a direct role in detaching clathrin-coated vesicles from the plasma membrane [6,7] but it has recently been proposed to have a role as a switch to regulate the endocytic step [8]. So far, at least three different dynamin genes have been found with different expression patterns and possibly different functions.…”
Section: Introductionmentioning
confidence: 99%